1970
DOI: 10.4314/ijest.v3i9.8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on a vapour compression system using nanorefrigerants

Abstract: Convective heat transfer is very important in the HVAC, refrigeration and microelectronics cooling applications. R134a is most widely adopted alternate refrigerant in refrigeration equipment, such s domestic refrigerators and air conditioners. Though the global warming up potential of R134a is relatively high, it is affirmed that it is a long term alternate refrigerants in lots of countries. The addition of nanoparticles to the refrigerant results in improvements in the thermophysical properties and heat trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(66 citation statements)
references
References 12 publications
2
58
0
2
Order By: Relevance
“…The uses of nanoparticle in refrigerant/lubricant mixture in improving coefficient performance/cooling capacity in refrigeration system were done by few researchers [4][5][6][7][8][9][10]. For example, Bi, et al [3] conducted experiment of mineral oil with TiO 2 nanoparticles mixtures as lubricant in domestic refrigerator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uses of nanoparticle in refrigerant/lubricant mixture in improving coefficient performance/cooling capacity in refrigeration system were done by few researchers [4][5][6][7][8][9][10]. For example, Bi, et al [3] conducted experiment of mineral oil with TiO 2 nanoparticles mixtures as lubricant in domestic refrigerator.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the power consumption decreased by 2.4% and the COP was enhanced up to 4.4%. Subramani and Prakash [7] dispersed Al 2 O 3 in MO. It is observed that by using Al 2 O 3 /R134a/MO nanorefrigerant, the power consumption was reduced by 25 % and up to 1.53 enhancement factor in the evaporator was attained.…”
Section: Introductionmentioning
confidence: 99%
“…For the nonsuperheating/subcooling case, the variation of COP, the compressor work per unit mass ( comp ), the evaporator heat per unit mass ( ), and the condenser heat per unit mass ( ) with condensation temperature ( ) are presented in Figures 2, 3, and 4 at evaporation temperatures of 0 ∘ C, −10 ∘ C, and −20 ∘ C, respectively. At 5 ∘ C in the superheating/subcooling case, the variation of COP, the compressor work per unit mass ( comp ), the evaporator [14] for the validation process of current study. heat per unit mass ( ), and the condenser heat per unit mass ( ) with the condensation temperature ( ) are presented in Figures 5, 6, and 7 according to the evaporation temperatures of 0 ∘ C, −10 ∘ C, and −20 ∘ C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…T fd (˝C) Subramani et al [44] conducted experimental studies on an R134a refrigeration system by introducing a mixture of mineral oil and alumina nanoparticles instead of POE (polyolester) oil. The authors found that the freezing capacity was higher, and power consumption reduced by 25%.…”
Section: Proportion (G/l)mentioning
confidence: 99%